Effects of winter wheat cover crop desiccation times on soil moisture, temperature and early maize growth - B. Stipešević; E.J. Kladivko (Plant, Soil and Environment, 2005)
Two tillage systems for maize (Zea mays) after soybean (Glycine max), no-till (NT) and conventional till (CT), which consisted of double disking in the spring, were included in the experiment on two sites in Indiana, USA. Each tillage plot had three winter wheat (Triticum aestivum L.) cover crop levels: no cover crop (N), early desiccation (E), 3-4 weeks prior to planting the maize, and regular desiccation (R), within the maize planting week. Due to the mulching effect, both E and R for both tillage systems increased soil moisture, except in the case of spring drought, when E proved dominant. Soil temperature for both tillage systems showed N > E > R order. Young maize plants tended to grow taller and have greater shoot biomass in NT than in CT. Both E and R improved early maize growth. In the case of drought, the E proved significantly better for maize on both tillage treatments, due to the better soil water conservation, therefore the winter wheat cover crop should be desiccated early in given climate conditions.